2020
DOI: 10.3390/antiox9121287
|View full text |Cite
|
Sign up to set email alerts
|

Association of Antioxidants Use with All-Cause and Cause-Specific Mortality: A Prospective Study of the UK Biobank

Abstract: Prospective studies and randomized controlled trials elucidating the impact of antioxidants supplementation on mortality risk are inconclusive. The present analysis determined association between regular antioxidants use and all-cause (primary objective), as well as cause-specific, mortality in 345,626 participants of the UK Biobank cohort using Cox proportional hazard models. All models were adjusted for confounders and multiple testing. Antioxidants users were defined as participants who indicated to regular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…2. Similar to a previous study (20) , the following exclusion criteria were applied: 1) malabsorption/celiac disease, 2) missing lifestyle risk factors (physical activity and/or smoking status), 3) missing socioeconomic factors (Townsend deprivation index, total household income, ethnic background, highest qualification, and/or overall health rating), 4) missing data of the physical exam (body mass index (BMI), systolic blood pressure (SBP)), 5) history of diabetes mellitus, 6) implausible energy or carbohydrate intake, i.e., being in the upper 0.1 % of total energy and/or carbohydrate intake or total energy intake <1.1 × basal metabolic rate -500 kcal (under-reporting) or >2.5 × basal metabolic rate + 500 kcal (over-reporting) resulting in a study population of 186,811 participants (Supplementary Fig. 2 and 3).…”
Section: Study and Participantssupporting
confidence: 88%
“…2. Similar to a previous study (20) , the following exclusion criteria were applied: 1) malabsorption/celiac disease, 2) missing lifestyle risk factors (physical activity and/or smoking status), 3) missing socioeconomic factors (Townsend deprivation index, total household income, ethnic background, highest qualification, and/or overall health rating), 4) missing data of the physical exam (body mass index (BMI), systolic blood pressure (SBP)), 5) history of diabetes mellitus, 6) implausible energy or carbohydrate intake, i.e., being in the upper 0.1 % of total energy and/or carbohydrate intake or total energy intake <1.1 × basal metabolic rate -500 kcal (under-reporting) or >2.5 × basal metabolic rate + 500 kcal (over-reporting) resulting in a study population of 186,811 participants (Supplementary Fig. 2 and 3).…”
Section: Study and Participantssupporting
confidence: 88%
“…Consumption of sugar and sugar subtypes was calculated based on the Oxford WebQ data with methodology similar to recent studies [ 27 , 28 ]. In brief, energy and total sugar contents were estimated for each Oxford WebQ questionnaire item based on McCance and Widdowson’s The Composition of Foods and its supplements [ 26 ], the UK Data Archive Standard Recipes Database [ 29 ], and product labels.…”
Section: Methodsmentioning
confidence: 99%
“…Other bioactive compounds, such as antioxidants, could also exert protective effects againts cancer mortality by mitigating the impact of oxidative stress on the body. A potential association between non-recent use of antioxidant vitamin supplements and vitamin C and cancer mortality prevention was observed in EPIC [55], but this association remains controversial in light of a research study conducted in the UK-Biobank cohort (n = 10,780 cancer deaths) that found different results [83]. A diet rich in vitamin K was also associated with reduced mortality for all cancers in one EPIC study [52], but not in another country-based EPIC study [53].…”
Section: Protective Factors Against Cancer Mortalitymentioning
confidence: 99%